2020
DOI: 10.3390/ijms21124294
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Models and Assays to Study NLRP3 Inflammasome Biology

Abstract: The NLRP3 inflammasome is a multi-protein complex that initiates innate immunity responses when exposed to a wide range of stimuli, including pathogen-associated molecular patterns (PAMPs) and danger-associated molecular patterns (DAMPs). Inflammasome activation leads to the release of the pro-inflammatory cytokines interleukin (IL)-1β and IL-18 and to pyroptotic cell death. Over-activation of NLRP3 inflammasome has been associated with several chronic inflammatory diseases. A deep knowledge of NLRP3 inflammas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 134 publications
(220 reference statements)
0
26
1
Order By: Relevance
“…Therefore, THP-1 cells have been widely used as a suitable in vitro model of human macrophages in mechanistic studies of external stimuli. Macrophages are used as model cell lines to research inflammasome activation for therapeutic and/or mechanistic studies [25]. The upper airways, including the nasopharynx and paranasal sinuses, have been shown to be a silent reservoir for P. aeruginosa [26].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, THP-1 cells have been widely used as a suitable in vitro model of human macrophages in mechanistic studies of external stimuli. Macrophages are used as model cell lines to research inflammasome activation for therapeutic and/or mechanistic studies [25]. The upper airways, including the nasopharynx and paranasal sinuses, have been shown to be a silent reservoir for P. aeruginosa [26].…”
Section: Discussionmentioning
confidence: 99%
“…Different techniques could be used to study NLRP3 inhibitors [ 47 ]; the use of differentiated THP-1 cells treated with NLRP3 activating stimuli is suitable for the screening of large series of compounds [ 48 ]. All the synthesised compounds ( Figure 2 ) were evaluated for their NLRP3 inhibitory activity by measuring their ability to prevent NLRP3-dependent pyroptosis in differentiated THP-1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…We used acute glucose shift conditions as changes between 5 mM and 25 mM glucose to emulate the commonly observed glycemic variability owing to postprandial hyperglycemia in patients with type 2 diabetes, rather than rare severe hypoglycemia. Owing to the difficulties in collecting human primary monocytes, the THP-1 monocyte-like cell line, derived from acute monocytic leukemia, has been extensively used in the study of NLRP3 inflammasome biology, despite its tumoral origin [28]. Emerging evidence has indicated that the activation of the NLRP3 inflammasome might lead to the maturation and secretion of IL-1β, which has been implicated in the pathological development of type 2 diabetes and cardiovascular diseases [29].…”
Section: Discussionmentioning
confidence: 99%